(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Geography is a key element in strategic thinking and is an important source to explain strategic culture. There are many misconceptions about India’s strategic culture, perhaps because it has not been clearly articulated and its security environment is relatively unsettled. The country is both a continental and maritime nation. Its geography offers a number of explanations to its insular nature, sense of civilization and destiny. As the country did not inherit clearly demarcated borders on Independence, its reliance on its frontiers being bastions for defence and security has proved delusive. A deeper understanding of the nature of terrain along its borders is necessary. India’s maritime heritage and responsibilities are also based on its geographic location. While geography remains unchanging, it is the shape of human behaviour that has changed geo-political equations.